2019
DOI: 10.1016/j.celrep.2019.08.069
|View full text |Cite
|
Sign up to set email alerts
|

Multilayered Control of Protein Turnover by TORC1 and Atg1

Abstract: Graphical Abstract Highlights d S. cerevisiae proteins harbor a minimum of 45,000 distinct phosphorylation sites d TORC1 and Atg1 regulate at least 26 protein and lipid kinases d Atg1 phosphorylates upstream regulators of TORC1 d TORC1 phosphorylates Atg29 to inhibit autophagy SUMMARYThe target of rapamycin complex 1 (TORC1) is a master regulator of cell homeostasis, which promotes anabolic reactions and synchronously inhibits catabolic processes such as autophagy-mediated protein degradation. Its prime autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
109
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(118 citation statements)
references
References 110 publications
(113 reference statements)
9
109
0
Order By: Relevance
“…The majority of the identified p-peptides (77%) feature a single p-site ( Figure 1D) and have a phosphorylation situated primarily on serine (S) (78%) and to a lesser extent on a threonine (T) (19%) or tyrosine (Y) residue (3%) ( Figure 1E). Overall, the obtained results and data metrics are congruent with previously published phosphoproteomics (Hu et al, 2019;Oliveira et al, 2015;Paulo and Gygi, 2015) and proteomics data (Figure S1) (Casanovas et al, 2015). Furthermore, by stringent statistical filtering, we found that the abundance of 7,922 p-peptides (55%) belonging to 1,792 phosphoproteins is significantly changed (q-value < 0.01) by >2-fold at least at one time point relative to the exponential phase (6 h) ( Figure 1C).…”
Section: Quantitative Phosphoproteomics Analysis Of the Yeast Life Cyclesupporting
confidence: 90%
“…The majority of the identified p-peptides (77%) feature a single p-site ( Figure 1D) and have a phosphorylation situated primarily on serine (S) (78%) and to a lesser extent on a threonine (T) (19%) or tyrosine (Y) residue (3%) ( Figure 1E). Overall, the obtained results and data metrics are congruent with previously published phosphoproteomics (Hu et al, 2019;Oliveira et al, 2015;Paulo and Gygi, 2015) and proteomics data (Figure S1) (Casanovas et al, 2015). Furthermore, by stringent statistical filtering, we found that the abundance of 7,922 p-peptides (55%) belonging to 1,792 phosphoproteins is significantly changed (q-value < 0.01) by >2-fold at least at one time point relative to the exponential phase (6 h) ( Figure 1C).…”
Section: Quantitative Phosphoproteomics Analysis Of the Yeast Life Cyclesupporting
confidence: 90%
“…Consistent with this, deletion of Snx4 results in insufficient PAS formation and a delayed autophagic response [138]. In a more recent phosphoproteomics study, Snx4 was identified as a direct substrate for Atg1 [139]. This phosphorylation event may direct Snx4 away from its physiological functions in endosomal sorting and selective autophagy and towards its role in starvation-induced autophagy.…”
Section: Sorting Nexins In Non-selective Autophagy In Yeastmentioning
confidence: 62%
“…Starvation induces autophagy in part through deactivation of the nutrient-sensing TORC1 kinase. Deactivation of TORC1 promotes the recruitment of the most upstream set of autophagy-regulating proteins, members of the ATG1 complex, to the phagophore assembly site (PAS) (Hu et al, 2019). ATG1 not only promotes autophagy induction, but may also facilitate late stages of auto-phagosome biogenesis (Kijanska and Peter, 2013).…”
Section: The Upregulation Of the Autophagy Pathwaymentioning
confidence: 99%